Comparative Study of Problem-Based and Project-Based Learning on Economic Learning Outcomes in Classes XA and XB at State High School 2 Tondano - Kandori, Iwan (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The purpose of this study is to determine the comparison of Economic Learning Achievement Using the Problem Based Model. Learning and Project Based Learning on the Learning Achievement of Economics Class XA and XB of SMA Negeri 2 Tondano. This study uses a quantitative method with a quasi- experimental research design or one- way group pretest-posttest. The sample of this study was 25 students of class XA and XB of SMA Negeri 2 Tondano in the 2024/2025 academic year. Data collection was carried out through descriptive tests Pretest and Posttest. The results of the study showed an increase in Learning Achievement in Economics subjects which was higher in the Problem Based model. Learning where the Pretest Value is 39.6 and the Posttest Value is 86.4, while in the Project Based Model Learning obtained a Pretest Value of 38.2 and a Posttest Value of 84.6. Overall, the Problem Based Model Learning shows more improvement which includes student enthusiasm, the formation of heterogeneous groups, information organization, and the ability to work together in problem solving. As for the Project Based Model Learning enhancement includes student engagement, active participation, problem awareness, ability to work together, and project presentation. Both models are seen each has its own advantages and is able to improve student learning achievement at SMA Negeri 2 Tondano.